Effective in Vitro Photokilling by Cell-Adhesive Gold Nanorods - Artiga, Álvaro; García-Embid, Sonia; De Matteis, Laura; Mitchell, Scott G.; de la Fuente, Jesús M. (Frontiers in Chemistry, 2018)
Upon excitation of their localised surface plasmon resonance (LSPR) band, gold nanorods (AuNRs) show a characteristic light-to-heat transduction, a useful and versatile property for a range of biomedical applications such as photothermal therapy, drug delivery, optoacoustic imaging and biosensing, among others. Nanoparticle (NP)-mediated photothermal therapy (PTT) rests on the ability of nanomaterials to convert light energy into heat and can currently be considered as a promising method for selectively destroying tumour cells by (photo)-thermoablation. One inherent limitation to NP-mediated PTT is that the nanoparticles must arrive at the site of action to exert their function and this typically involves cellular internalisation. Here we report the use of the Keggin-type polyoxometalate (POM) phosphotungstic acid (PTA) as an inorganic gelling agent for the encapsulation of plasmonic gold nanorods (AuNRs) inside a biocompatible and cell-adhesive chitosan hydrogel matrix. These functional sub-micrometric containers are non-cytotoxic and present the ability to adhere to the cytoplasmic membranes of cells avoiding any need for cellular internalisation, rendering them as highly efficient thermoablating agents of eukaryotic cells in vitro.